DNA methylation at birth is associated with lung function development until age 26 years. Issue 4 (15th April 2021) - Mukherjee, Nandini; Arathimos, Ryan; Chen, Su; Kheirkhah Rahimabad, Parnian; Han, Luhang; Zhang, Hongmei; Holloway, John W.; Relton, Caroline; Henderson, A. John; Arshad, Syed Hasan; Ewart, Susan; Karmaus, Wilfried
Little is known about whether DNA methylation (DNAm) of cytosine–phosphate–guanine (CpG) sites at birth predicts patterns of lung function development. We used heel prick DNAm from the F1-generation of Isle of Wight birth cohort (IOWBC-F1) for discovery of CpGs associated with lung function trajectories (forced expiratory volume in 1 s, forced vital capacity, their ratio, and forced expiratory flow at 25–75% of forced vital capacity) over the first 26 years, stratified by sex. We replicated the findings in the Avon Longitudinal Study of Parents and Children (ALSPAC) using cord blood DNAm. Epigenome-wide screening was applied to identify CpGs associated with lung function trajectories in 396 boys and 390 girls of IOWBC-F1. Replication in ALSPAC focussed on lung function at ages 8, 15 and 24 years. Statistically significantly replicated CpGs were investigated for consistency in direction of association between cohorts, stability of DNAm over time in IOWBC-F1, relevant biological processes and for association with gene expression (n=161) in IOWBC F2-generation (IOWBC-F2). Differential DNAm of eight CpGs on genes GLUL, MYCN, HLX, LHX1, COBL, COL18A1, STRA6, and WNT11 involved in developmental processes, were significantly associated with lung function in the same direction in IOWBC-F1 and ALSPAC, and showed stable patterns at birth, aged 10 and 18 years between high and low lung function trajectories in IOWBC-F1. CpGs on LHX1 and COL18A1 were linked to gene expression in IOWBC-F2. In two large cohorts, novel DNAm at birth were associated with patterns of lung function in adolescence and early adulthood providing possible targets for preventative interventions against adverse pulmonary function development. In two population-based cohort studies differentially methylated genomic sites at birth associated with lung function from age 10 to 26 years were discovered and replicated. These sites were located on genes involved in lung morphogenesis. https://bit.ly/37qtT6Z